REMOTE WORKING AND WORK-FAMILY CONFLICT DURING THE COVID-19 OUTBREAK - Tülay Turgut; Asiye Yüksel Ağargün (İşletme Bilimi Dergisi)
Aim: The COVID-19 outbreak started a new era as it changed the balance between work and family by necessitating remote working. However, only a few studies have investigated work-family conflict during the pandemic. Hence, the primary aim of this study is to examine work arrangement and work-family conflict relationship. It is also expected that gender will have a moderating role that affects work-family conflict in different ways depending on work arrangements. The second purpose of the study is to explore the aspects that facilitate working from home.Method: The sample consisted of 245 employees working in finance and information sectors in Turkey. Data was collected by using questionnaires.Findings: Results indicated that office workers had higher work-to-family conflict than remote workers and hybrid workers. No significant difference was found on family-to-work conflict regarding the work arrangement, and gender did not act as a moderator. Regarding the second purpose of the study, the aspects that facilitate working from home were classified into three categories. In the content analysis, the most repeated codes were related to working conditions, followed by physical and psycho-social needs.Results: This research is one of the first investigations in Turkey to explore the relationship between work arrangement and work-family conflict during the COVID-19 outbreak providing important results regarding the remote working arrangements adopted by many organizations worldwide.